Pengaruh Implementasi Good Corporate Governance dan Strategi Bisnis terhadap Kinerja Perusahaan: Studi Kasus BUMN di Indonesia Tahun 2013-2018 - Ichwan Lazuardi Natapermana; Winwin Yadiati; Euis Nurhayati (Jurnal Maksipreneur, 2020)
State-Owned Enterprise (SOE) is one of the agents of economic activity in the national economy of Indonesia that has an important role in managing the national economy to realize the welfare of society. At present, SOEs have often received critical attention from the public because they are seen as inefficient, wasteful of resources utilization, laden with corruption, and have lower level profitability. The implementation of Good Corporate Governance (GCG) and the right of business strategy is expected to improve the performance of SOEs both financially and non-financially. The purpose of this study was to determine the effect of GCG implementation and business strategy on firm performance. In this study, financial performance was measured using Return on Equity (ROE) and non-financial performance used Customer Satisfaction Index (CSI). The method used in this research was a partial regression of panel data through the determined of the estimation model after the classical assumption test. The sample used in this study was 22 SOEs (BUMN) that met the sample criteria. The results showed that there was a significant effect of the implementation of GCG on ROE and CSI. But, there was not a significant effect of the implementation of its’ business strategies on ROE, otherwise the significant effect on CSI.